2017
DOI: 10.5047/agbm.2017.00702.0025
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Chemical Structures of Organic Matrices and Their Functions in the Biomineralization Processes of Molluscan Shells

Abstract: Keywordscalcium carbonate and an organic matrix. In the course of shell formation, the periostracum, which is not mineralized and covers the external surface of the shell, is formed first; subsequently, the prismatic layer is formed on the periostracum. Finally, the nacreous layer is formed on the prismatic layer (Checa 2000). The nacreous layer is made of tablets of aragonite single crystals. The aragonite crystal compartment in the nacreous layer is sandwiched between sheets of organic matrix. In contrast, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…NLP is known to be important for calcium ion uptake for biomineralization while also serving as a checkpoint or negative regulator of calcification (Miyamoto et al, 2005; Takakura et al, 2008). Laminin aids in biomineralization by aiding nucleation, potentially due to its calcium carbonate‐binding activity (Suzuki et al, 2017). A cell surface hyaluronidase (cemip2) coding gene, which is known to aid shell nucleation, was also upregulated (Lopes‐Lima et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…NLP is known to be important for calcium ion uptake for biomineralization while also serving as a checkpoint or negative regulator of calcification (Miyamoto et al, 2005; Takakura et al, 2008). Laminin aids in biomineralization by aiding nucleation, potentially due to its calcium carbonate‐binding activity (Suzuki et al, 2017). A cell surface hyaluronidase (cemip2) coding gene, which is known to aid shell nucleation, was also upregulated (Lopes‐Lima et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In both BMSP and Pif, no domain was detected. Some searches would detect only the repetitive lowcomplexity domains (RLCD) which designates a possibility that the particular region used to have a domain, but has probably degraded down and thus only recognizable partially at the sequence level (Suzuki et al, 2017;Setiamarga et al, 2021a;. We also predicted the stereostructures of some representatives of BMSP (Mytilus galloprovincialis), Pif (A. argo,N.…”
Section: The Evolution Of Shell and Eggcase Matrix Proteins Through Independent Recruitments Losses And Domain Changes Allows A Argo To Omentioning
confidence: 87%
“…The models of BMSP/LamG3/Pif proteins predicted by AlphaFold2 indicate that the region where no domain was detected in the proteins (except for the LamG3 proteins) actually still retains enough of its LamG3 domain characteristics (Figure 5). LamG3 domain is a receptor for various extracellular matrix proteins, which function is mediated by the calcium ion (Tryggvason 1993;Yurchenco et al 1993;Yu and Talts 2003;Klees et al, 2008;Suzuki et al, 2017). This thus might explain the usefulness of the domain not only for the formation of calcified structures but also for other functions, while at the same time also suggests the unnecessity of the organisms compared to retain or use all of the BMSP/LamG3/Pif protein homologs for the same function, which might thus also explain why Cephalopods (Nautilus) only use LamG3 for their shell formation, and why the argonauts also re-recruited this protein to form their eggcase.…”
Section: The Evolution Of Shell and Eggcase Matrix Proteins Through Independent Recruitments Losses And Domain Changes Allows A Argo To Omentioning
confidence: 99%
“…Each upper nucleus grows into a thin aragonite tablet along with an organic sheet. A previous study has reported that when Pif, the matrix protein associated with the aragonite formation of the nacreous microstructure in P. fucata , is knocked down, the lamellar structure becomes disordered because of the early formation of the tablets on the upper layer before the tablets on the lower layer completely form 24 . Knockdown of Pif decreased the secretion of Pif.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is difficult to analyse the detailed structure and function of these proteins. In previous reports, from the acid (or EDTA)-soluble fraction or denaturing regent (SDS, DTT and urea)-soluble fraction, the various proteins have been identified 24 , 25 . For example, nacrein 10 , pearlin 13 , 14 , N19 26 , 27 , Pif 12 in the nacre, prismalin-14 15 , prismin 16 , shematrins 28 in the prism and LICP 17 in the ligament.…”
Section: Discussionmentioning
confidence: 99%